Teachers' perception towards the use of group work activities in ESL classroom at SMK Petra Jaya / Hayati Edward - Edward, Hayati (2008)
The purpose of the study was to investigate teachers' perceptions on the use of group work teaching and learning in classrooms and to find out whether they perceived the implementation of group work in KBSM programme as feasible. It is also to examine problems faced by teachers in conducting group work activities and to identify these problems. The theory that lies in this study is based on Vygotsky's "Zone of Proximal Development" or ZPD which emphasizes that learning is, fundamentally, a socially mediated activity. A non-experimental research in the form of a survey was conducted to achieve the purpose. The study focuses on four perspectives which influence teachers' perceptions on the implementation of group work in an ESL classroom; the Group Structure, the Designated Time, the Amount of Material and the Level of Complexity. The subjects in the study were fourteen English teachers teaching English to the Transistion, Form 1, Form 2, Form 3, Form 4 and Form 5 students in SMK Petra Jaya. All the subjects were asked to answer a questionnaire and be involved in an interview. Three observations in three different classes using group work strategy were also carried out for the data collection. Findings from the study showed that teachers do perceive group work strategy as feasible under the KBSM concept of Communicative Approach in language teaching and learning. However, some teachers are rather reluctant to use group work strategy regularly in classrooms due to the constraint of time, the big classes and other factors.